The Mediating Role of Perceived Information Quality and Destination Image in the Influence of Generated Content on Tourists’ Intention to Visit - Luthfiamer Luthfiamer; Maria Apsari Sugiat; Anton Mulyono Azis (Ekonomis: Journal of Economics and Business, 2026)
This study aims to examine the influence of generated content on tourists’ intention to visit Derawan Islands by employing the Stimulus-Organism-Response (S-O-R) theoretical framework. In this model, generated content, both user-generated (UGC) and firm-generated content (FGC), acts as a stimulus that affects tourists’ perceptions of information quality (perceived information quality) and destination image, which in turn influence their intention to visit. The research is motivated by the significant decline in Indonesia’s tourism sector due to the COVID-19 pandemic, which also impacted the Derawan Islands through reduced international tourist visits. In the post-pandemic context, tourist behavior and preferences have shifted considerably, with increasing demand for credible and engaging digital information. This study employs a quantitative approach to assess the relationships between these variables. The findings indicate that generated content has a significant positive effect on both perceived information quality and destination image, which serve as mediators influencing tourists’ intention to visit. These results highlight the importance of content-driven digital marketing strategies in restoring the attractiveness of tourism destinations. This research offers theoretical contributions to the development of digital tourism literature and practical insights for destination managers seeking to enhance their promotional effectiveness in the digital era.